Dry eye disease treatment: the role of tear substitutes, their future, and an updated classification - Barabino, S; Benitez-Del-Castillo, J M; Fuchsluger, T; Labetoulle, M; Malachkova, N; Meloni, M; Utheim, T P; Rolando, M (European review for medical and pharmacological sciences, 2020)
The aim of this review is to summarize the results of a consensus meeting held by a group of experts in dry eye disease (DED) to discuss the importance of tear substitutes in the treatment of DED. The meeting focused especially on the main characteristics of lacrimal substitutes, the development of in vitro models to investigate DED pathophysiology and treatment, the importance of conducting rigorous clinical trials, the requirements of the upcoming European Legislation on medical devices, the advances in the formulation of safer preservatives, the peculiarities of treatment in younger subjects, and the importance of an updated terminology for lacrimal substitutes. A literature search was conducted using MEDLINE, with different combinations of pertinent keywords, depending on the subject under discussion, such as "dry eye disease"; "tear substitutes"; "in vitro models"; "ocular surface"; "clinical trials"; "European Regulation"; "preservatives" "younger patients". Also, each author included in the discussion selected articles from their personal library. Using a consensus-based method called nominal group technique to reach a conclusion and proposal for a new classification of eye drops used to improve the tear film and ocular surface epithelia, the experts also conducted a round table meeting. The new terms proposed by the authors are "wetting agents", "multiple-action tear substitutes" or "ocular surface modulators". The new classification is needed to distinguish eye drops used to improve the tear film and ocular surface epithelia, in line with the new definition of DED, which recognizes the loss of ocular homeostasis, and the creation of a vicious circle of chronic inflammation and ocular damage as fundamental aspects of DED pathophysiology. Although tear substitutes have been historically used to provide eye lubrication to the ocular surface, recent advances in the pathophysiology of dry eye disease (DED) clarified that treatment should not just focus on tear film quality or quantity, but address the loss of homeostasis of the ocular surface, blocking the vicious circle of chronic inflammation and ocular damage. Given the scant comparative evidence on tear substitutes currently on the market, further studies should focus on developing new agents, considering the advantages provided by in vitro models, importance of conducting rigorous clinical trials, availability of less harmful preservatives and obligations related to the new European legislation on medical devices. Based on the discussion of these topics, a group of experts held a consensus meeting to identify new and more appropriate terms for different tear substitutes. The proposed terms are wetting agents, multiple-action tear substitutes and ocular surface modulators. Regardless of the agent used, it is important to note that tear substitutes represent one of many options for DED treatment, which should not overlook the psychological aspects of the disease and the peculiarities of younger subjects, who seem to have a higher risk for DED, possibly related to digital devices excessive use.